The consumption of fish by the riverine population of the lower Solimões River, Amazonas, Brazil - G. K. S. Dias; F. K. Siqueira-Souza; L. A. Souza; C. E. C. Freitas (Brazilian Journal of Biology, 2023)
Abstract The riverine population of the Amazon Basin are among the largest consumers of fish in the world, but the consumption patterns could be regionally distinct. Moreover, their total fish catches are not fully known. The objective of this work was to estimate the per capita fish consumption of the riverine people that inhabit the Paciência Island (Iranduba, Amazonas), where there is a fishing agreement in force. A total of 273 questionnaires were applied during the first two weeks of each month between April 2021 and March 2022. The sample unit was the residences. The questionnaire contained questions about the species captured and their quantities. Consumption was calculated by dividing the average monthly capture with the average number of residents per household interviewed, which was multiplied by the number of questionnaires applied. Thirty groups of consumed fish species belonging to 17 families and 5 orders were recorded. The total catch was 3,388.35 kg and the highest monthly catch was 602.60 kg during the falling-water season in October. Daily per capita fish consumption averaged 66.13 ± 29.21 g/day, with a peak of 116.45 g/day during the falling-water season in August. The high fish consumption rate highlighted the importance of fisheries management to food security and the maintenance of the community’s lifestyle.